(779) Foreign Loans and Economic development (Part 1): Restatement of Qayum's Model القروض الأجنبية والتنمية الاقتصادية: الجزء الأول: إعادة صياغة نموذج قيوم - M. El-Imam, M. (INP, 2023)
The study explores Mr. Qayum’s model for evaluating loan advantages considering gestation periods and repayment lags. It presents a mathematical framework defining the advantage criterion to assess financial efficiency, refining the model to incorporate time delays and loan replacement factors. The research discusses the impact of these elements on investment decisions, presenting key values of the criterion and relevant variables. The study concludes with practical recommendations for financial institutions and investors to optimize lending and replacement strategies.